Complete Genome and Comparative Genome Analysis of Lactobacillus reuteri YSJL-12, a Potential Probiotics Strain Isolated From Healthy Sow Fresh Feces. (July 2020) - Xu, Su; Cheng, Jianjun; Meng, Xiangchen; Xu, Yan; Mu, Ying
Lactobacillus reuteri YSJL-12 was isolated from healthy sow fresh feces and used as probiotics additives previously. To investigate the genetic basis on probiotic potential and identify the genes in the strain, the complete genome of YSJL-12 was sequenced. Then comparative genome analysis on 9 strains of Lactobacillus reuteri was performed. The genome of YSJL-12 consisted of a circular 2, 084, 748 bp chromosome and 2 circular plasmids (51, 906 and 15, 134 bp). From among the 2065 protein-coding sequences (CDSs), the genes resistant to the environmental stress were identified. The function of COG (Clusters of Orthologous Group) protein genes was predicted, and the KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways were analyzed. The comparative genome analysis indicated that the pan-genome contained a core genome of 1257 orthologous gene clusters, an accessory genome of 1064 orthologous gene clusters, and 1148 strain-specific genes, and the antibacterial mechanism among Lactobacillus reuteri strains might be different. The phylogenetic analysis and genomic collinearity revealed that the phylogenetic relationship among 9 strains of Lactobacillus reuteri was connected with host species and showed host specificity. The research could help us to better predict genes function and understand genetic basis on adapting to host gut in Lactobacillus reuteri YSJL-12.